2021
DOI: 10.1016/j.nicl.2021.102661
|View full text |Cite
|
Sign up to set email alerts
|

Disorder- and emotional context-specific neurofunctional alterations during inhibitory control in generalized anxiety and major depressive disorder

Abstract: Highlights fMRI affective GO/NOGO tasks differentiates depression (MDD) from anxiety (GAD). MDD but not GAD showed impaired inhibitory control on the behavioral level. MDD exhibited decreased engagement of posterior frontal/mid-cingulate regions. The neural alterations were specific for MDD and inhibition in negative contexts. GAD showed intact inhibition and enhanced dlPFC activity relative to MDD.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Notably, both GAD and MDD exhibited smaller GMV in the mPFC in comparison to 13 FAD. fMRI studies have shown common neurofunctional alterations in the mPFC and ACC in cognitive or emotional processing in both GAD and MDD (17)(18)(19). Previous metaanalyses have identified altered volume in mPFC in GAD (22), MDD (26), and individuals with high neuroticism (48), a pathological meta-factor associated with GAD and MDD which share symptomatic (e.g., negative affect, worry) (4) and genetic etiologies (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, both GAD and MDD exhibited smaller GMV in the mPFC in comparison to 13 FAD. fMRI studies have shown common neurofunctional alterations in the mPFC and ACC in cognitive or emotional processing in both GAD and MDD (17)(18)(19). Previous metaanalyses have identified altered volume in mPFC in GAD (22), MDD (26), and individuals with high neuroticism (48), a pathological meta-factor associated with GAD and MDD which share symptomatic (e.g., negative affect, worry) (4) and genetic etiologies (5).…”
Section: Discussionmentioning
confidence: 99%
“…While the segregation has been translated into the Acute Threat (fear) and Potential Threat (Anxiety) domains of the Research Domain Criteria (RDoC) (12), accumulating findings indicate a shared neural basis anxiety, fear and general negative affect (13,14). Shared and distinct neurobiological systems underlying these pathological domains have been revealed by functional magnetic resonance imaging (fMRI) studies comparing GAD and FAD (15,16), as well as GAD and MDD during emotional and cognitive processing (17)(18)(19) or by case-control studies examining brain structural alterations using structural MRI (sMRI) in single diagnostic categories (20). However, results have been dependent on the specific task-domain and population examined and conclusions have been limited by small sample sizes and analytic variability (21).…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic and epidemiological perspectives suggest that generalized anxiety disorder (GAD) and major depressive disorder (MDD) share symptoms of general affective distress and exhibit high rates of co-morbidity (70-90% lifetime comorbidity) leading to ongoing debates about common and distinct neurobiological bases (Maron and Nutt, 2017). Determining disorder-specific neural alterations in GAD and MDD can help understanding of the pathogenesis of these disorders and inform the development of more efficient interventions (MacNamara et al, 2017; Liu et al, 2021). An increasing number of studies have therefore adopted a transdiagnostic neuroimaging approach employing a direct comparison between GAD and MDD in order to determine common and disorder-specific neural alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the clinical symptoms of anxiety and depression are different. However, they are frequently presented simultaneously (Liu et al, 2021;Thorp et al, 2021). Importantly, there are lots of overlaps with respect of the pathophysiology and comorbidity of these two disorders.…”
Section: Introductionmentioning
confidence: 99%